Phytochemical Test and Antibacterial Test of Rhizopora apiculata Mangrove-Root against Escherichia coli and Staphylococcus aureus Bacteria - Usman Usman (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2017)
Indonesia has many kinds of mangrove but they have not been widely utilized as health food and medicinal products because of the limited information and research on the content of bioactive compounds in the mangroves. One of the mangrove species that are found in the Bontang mangrove forest, East Kalimantan is R. apiculata. It is used as fuel, building materials, shipbuilding, and as traditional medicine. This study aims to determine the class of secondary metabolites compounds and the antibacterial activity of methanol extract of R. apiculata mangrove roots. The extraction was performed by maceration method using methanol solvent. Secondary metabolites compounds class in the mangrove sample was determined qualitatively by using several phytochemical reagents. Antibacterial test against E. coli and S. aureus were performed using diffusion method with various concentration of the roots-mangrove methanol extract of 500, 250, and 125 ug/well. Incubation was performed in various time of 12, 24, 48 and 72 hours. Phytochemical test results showed that the roots-mangrove methanol extract of R. apiculata contained secondary metabolites classes of alkaloids, flavonoids and triterpenoids. The extract does not inhibit the growth of E. coli, but it could inhibit the growth of S. aureus at 500 ug / well with incubation time of 12, 24, 48 and 72 hours and have inhibition zones of 7.95 mm, 8.3 mm, 8.0 mm, and 7.0 mm, respectively. At a concentration of 250 ug/ well with an incubation time of 48 hours has a 7.5 mm of inhibition zone. Those inhibitions are relatively weak category.